Occurrence of Highly Conjugative IncX3 Epidemic Plasmid Carrying blaNDM in Enterobacteriaceae Isolates in Geographically Widespread Areas - Wang, Ya; Tong, Man-Ki; Chow, Kin-Hung; Cheng, Vincent Chi-Chung; Tse, Cindy Wing-Sze; Wu, Alan Ka-Lun; Lai, Raymond Wai-Man; Luk, Wei-Kwang; Tsang, Dominic Ngai-Chong; Ho, Pak-Leung (Frontiers in Microbiology, 2018)
The emergence of New Delhi metallo-beta-lactamase (NDM) in common enterobacterial species is a major concern for healthcare. Early reports have revealed that the spread of NDM involved diverse and heterogeneous plasmids. Recently, the involvement of a rare, IncX3 subtype plasmid has been increasingly recognized. Here, we studied the prevalence of IncX plasmid subtypes in 198 carbapenem-resistant Enterobacteriaceae, originating from a territory-wide active surveillance in Hong Kong in 2016. The complete sequences and biological features of the blaNDM-carrying plasmids were investigated. A total of 62 NDM-type, 21 OXA-48 type, 14 IMP-type, 8 KPC-type, 4 IMI-type producers and 89 non-carbapenemase-producers were tested for presence of IncX subtypes. IncX3 (n=60) was the most common subtype, followed by IncX4 (n=6) and IncX1 (n=2). The prevalence of IncX3 subtype in isolates producing NDM, other carbapenemase types and non-carbapenemase producers were 75.8%, 21.3% and 3.4%, respectively (P < 0.001). An IncX3 plasmid (size ~50 kb) was confirmed to carry blaNDM in 47 isolates of different enterobacterial species. Thirteen IncX3 plasmids originating from six healthcare regions in Hong Kong were completely sequenced. The results showed that the IncX3 plasmids carrying blaNDM share a high degree of sequence identity with a previously reported plasmid, pNDM-HN380 (GenBank accession JX104760), over the backbone and genetic load regions. A blast search further revealed the occurrence of identical or nearly identical IncX3 plasmids carrying blaNDM in other part of China, Korea, Myanmar, India, Oman, Kuwait, Italy and Canada. Two IncX3 carrying blaNDM were investigated further. Conjugation experiments demonstrated that the IncX3 plasmids could be efficiently transferred to multiple enterobacterial species at frequencies that are comparable or higher than the epidemic IncFII plasmid carrying blaCTX-M (pHK01). In addition, efficient transfer of the NDM plasmids occurred over a range of temperatures. In conclusion, this study demonstrated the important role played by IncX3 in the dissemination of NDM and the occurrence of pNDM-HN380-like plasmids in geographically widespread areas. The high mobility of IncX3 plasmid across different enterobacterial species highlights the ability of this plasmid replicon to be an important vehicle in worldwide dissemination of NDM.